Characterization of actinomycetes of marine sediment and their antagonistic activity against Vibrio sp. isolated from «whiteleg shrimp» Litopenaeus vannamei (Boone, 1931) - Tarazona J., Ulrike (2018)
The aim of the present study was to evaluate the antagonistic activity of a collection of 24 actinomycetes of marine sediment against wild species of Vibrio. Actinomycetes were characterized by their growth in Marine Agar and their extracellular enzymatic activity on different substrates. The antagonist activity was determined by in vitro tests against six strains of Vibrio isolated from Litopenaeus vannamei. Actinomycetes with greater antagonism were evaluated by their growth in standard ISP media and observations of microphotographs by scanning electron microscopy (SEM) techniques were done. The Vibrio strains were evaluated and identified by conventional biochemical techniques and confirmed by PCR. The results indicated that all actinomycetes showed at least some extracellular multi-enzymatic activity, predominating those that hydrolyze starch (79%). Antagonism tests indicated that 54% (13/24) of actinomycetes had anti-Vibrio activity, being the strains M10-77 and M11-116 (B) those that produced the largest inhibition halos. On the other hand, the sequence-based identification of the 16S rRNA gene corroborated the relationship of the isolated strains of L. vannamei with the genus Vibrio; likewise, some of these actinobacteria were identified as Streptomyces.